The five people you meet in heaven - Albom, Mitch 1958- (Sphere, 2004)
Weaves three stories about 83-year-old Eddie, the head maintenance person at Ruby Point Amusement park. Eddie meets 5 individuals in heaven each with a story to share, a secret to reveal and a lesson. The have profound meanings for Eddie on the real purpose of his life